Study of Antibacterial Activity of Green Betel Leaf (Piper betle L.) and Red Betel Leaf (Piper Crocatum L.) Extract Against Pseudomonas Aeruginosa Bacteria - Nailul Mukafiah (Universitas Muhammadiyah Malang, 2022)
Green betel leaf (Piper betle L.) and red betel leaf (Piper crocatum L.) are plants commonly used for traditional medicine. The betel plant can treat infections. Pseudomonas aeruginosa is a bacteria that causes nosocomial infections. This article's purpose is to describe previous research on the antibacterial activity of green betel leafextract (Piper betle L.) and red betel leaf (Piper crocatum L.) against Pseudomonas aeruginosa bacteria. We used a traditional review. A search in the literature was carried out by entering the keywords: Piper betle L., Piper crocatum L., Pseudomonas aeruginosa, and antibacterial in PubMed, Science Direct, and Google Scholar databases. Data sources were obtained online, then selected based on inclusion criteria, namely in the form of complete articles inIndonesian and English, explaining the extracts of green betel leaf (Piper betle L.) and red betel leaf (Piper crocatum L.) against both Pseudomonas aeruginosa bacteria in single or combination from the years 2008-2021. The search results for articles obtained were 344.122 articles, and 15 articles were included from various countries. The results showed that the extracts of green betel leaf (Piper betel L.) and red betel leaf (Piper crocatum L.) were able toinhibit Pseudomonas aeruginosa bacteria with strong to weak inhibition zones. Betel leaf extract (Piper betle) has been shown to have antibacterial properties and can inhibit Pseudomonas aeruginosa bacteria with strong to weak inhibition zones, single or combination from the years 2008-2021.